(untitled) (Medical Forum Monthly, 2024)
Objective: To determine association of macrosomia in pregnant women who have altered glycemic control. Study Design: Prospective cohort study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynaecologic Unit 2, Civil Hospital, Dow University of Health Sciences, Karachi from 04-09-2013 to 04-02-2014. Materials and Methods: Two thirty eight pregnant women were included in this study. 119 women who had abnormal HbA1c were in exposed group and 119 Women who had a normal HbAlC were taken as Non-Exposed Groups. Information from all patients were gathered through a pre- designed Proforma which include socio-demographics such as age, height weight as well as other study variables including booking status, gestational age, parity, history of macrosomic infants, history of diabetes in family, weight of baby. Results: Macrosomia was 2 time (Approximate of 1.59) more common in exposed than non-exposed group (RR: 1.59 95%CI: 1.29 to 2.02). Conclusion: We conclude that in this study woman with GDM mean HbA1c are significant predictors of newborn macrosomia. Early diagnosis and appropriate treatment of GDM aimed at tight control over maternal glucose levels positively influence the perinatal outcome and it prevents macrosomia.